TECHNOLOGY OF RECEIPT OF POWDER-LIKE GRADIENT MATERIALS FROM POWDERS AISI430 AND SAPONITE - Rud, V. D.; Khrystynets, N. A. (Visnyk of Vinnytsia Politechnical Institute, 2017)
The results of technological process of forming of filter gradient material have been presented on the basis of powders AISI430 and saponite with the use of vibrosegregation. This process will allow deciding the task of creation of fundamentally new materials with unique properties and their further use in production.